2012
DOI: 10.12681/mms.301
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of surface chlorophyll a in the Romanian near-shore waters

Abstract: Chlorophyll a (Chl a) dynamics in the near-shore waters of the NW Black Sea was investigated between 2002 and 2010 in the Mamaia Bay (north of Constanta, Romania) in relation to some physical-chemical parameters. Chl a ranged from values below detection limit (0.17 µg ) to 76.13 µg . l -1 , and showed large temporal variability (CV = 142.3%), strongly related to the Danube's discharges, meteorological conditions, and anthropogenic pressures.Seasonally, Chl a showed a winter/early spring maximum, sometimes foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…The influence of atmospheric deposition of IFN at the concentration of chlorophyll a in the surface waters in the Black Sea has never been studied. The previously published data have attributed spatial anomalies in the distribution of chlorophyll a to coastal sources of nutrients (Vasiliu et. al., 2012), physical flux of nutrients (Yunev et al, 2002), and dust deposition (Katara et al, 2008).…”
Section: Deposition Of Ifn and Mesoscale Processesmentioning
confidence: 99%
“…The influence of atmospheric deposition of IFN at the concentration of chlorophyll a in the surface waters in the Black Sea has never been studied. The previously published data have attributed spatial anomalies in the distribution of chlorophyll a to coastal sources of nutrients (Vasiliu et. al., 2012), physical flux of nutrients (Yunev et al, 2002), and dust deposition (Katara et al, 2008).…”
Section: Deposition Of Ifn and Mesoscale Processesmentioning
confidence: 99%
“…The core covers the typical Black Sea unit 1 (Piper and Calvert, 2011;Ross and Degens, 1974). The phytoplankton communities in the western Black Sea are typically dominated by dinoflagellates in spring, and diatoms and coccolithophores in fall (Eker et al, 1999;Moncheva et al, 2001), although the Romanian Shelf is generally dominated by diatoms with exceptions of blooms comprising cyanobacteria and dinoflagellates (Vasiliu et al, 2012). GSB have been reported from the chemocline of the Black Sea (e.g.…”
Section: Study Sites and Sample Collectionmentioning
confidence: 99%
“…In order to analyse spatial and temporal variations in the input of IFN to the Black Sea with atmospheric precipitations and to scale the effect of this input, we have followed Vautz et al (2003) to parameterize the concentration of IFN as a function of meteorological variables. A multiple regression equation is used in this model to bind meteorological parameters (daily data of the precipitations amount, wind direction, season and preceding dry period) with the flow of contaminants from the atmosphere.…”
Section: Multiple Regression Analysismentioning
confidence: 99%
“…In order to reconstruct a multiple nonlinear regression equation for the IFN concentration as a function of meteorological parameters, we have followed the approach discussed by Vautz et al (2003) and suggested by Brandon (1959). The method is based on (i) identification of regressions between the concentration of IFN and individual statistically significant meteorological variables and (ii) successive introduction of these individual regressions to the multiple regression equation.…”
Section: Multiple Regression Analysismentioning
confidence: 99%